ショウワ キチ デ ジュシン シタ ISIS エイセイ ニヨル VLF ソーサー ノ ATTENUATION BAND ト デンバ d. ジキケン ナイ ノ ULF・VLF ハドウ ダイ1カイ キョクチ ニオケル デンリケン ジキ ソウゴウ カンソク シンポジウム PART 2 - 渡辺, 成昭; ワタナベ, シゲアキ; 恩藤, 忠典; オンドウ, タダノリ; 中村, 義勝; ナカムラ, ヨシカツ; 村上, 利光; ムラカミ, トシミツ; WATANABE, Shigeaki; ONDOH, Tadanori; NAKAMURA, Yoshikatsu; MURAKAMI, Toshimitsu (国立極地研究所, 1979)
P(論文) 南極昭和基地で受信したISIS衛星のVLFテータ,およびハウスキーピンク用の磁力計テータにより,ソーサーの電場の方向が磁力線に直角方向にあることが分かった.電場の弱くなるattenuation bandの下限周波数は,通常ジャイロ周波数の整数倍てあり,まれに上限周波数がそれにあたる.低エネルギー粒子のサイクロトロン吸収によるものとすれば,950-1050 km付近に源がある. An analysis of the ISIS-VLF data and magnetic field data detected by house-keeping magnetometer received at Syowa Station, Antarctica, shows that the electric field component of the saucer emissions is approximately perpendicular to the local geomagnetic field lines. Lower cutoff frequencies of attenuation bands of the saucer emissions are usually at harmonics of the local proton gyrofrequencies (nG_p n=2, 3, 4.) around the ISIS satellite Sometimes, upper cutoff frequencies of the attenuation bands are observed at nG_p. The source region of saucers may be located at altitude of 950-1050 km which is estimated from the width of the attenuation bands, assuming that the attenuation bands of saucers are caused by the local cyclotron absorption of low energy protons departmental bulletin paper